Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia) - Vikhrev, Nikita E.; Sorokina, Vera S. (Zootaxa, 2017)
The Muscidae fauna of the Altai Republic, Russia, is discussed, and 28 species are newly recorded for the region. Six species (Hydrotaea hsiai Fan, 1965, Hydrotaea unispinosa Stein, 1898, Thricops aduncus Savage, 2003, Helina bispinosa Malloch, 1920, Helina obtusipennis (Fallén, 1823), Coenosia demoralis Huckett, 1965) are newly recorded for Russia. Three of these species (T. aduncus, H. bispinosa and C. demoralis) are newly recorded for the Palaearctic region. A description of the hitherto unknown female of Xestomyia atrox Sorokina & Pont, 2011 and redescriptions of Coenosia demoralis Huckett, 1965 and Hydrotaea hsiai Fan, 1965 are given. One new synonym is proposed: Phaonia fusca Meade, 1897 = Phaonia suspiciosa Stein, 1907, syn. nov.